The Potency of Azotobacter spp.Isolated from Tidal Land of South Kalimantan to Produce Indole Acetic Acids (IAA) - Fakhrur Razie; Anas Iswandi (Jurnal Ilmu Tanah dan Lingkungan, 2005)
Tidal land area is considered as the most frigile ecosystems. To open this area as agricultural land has to be donecarefully. To reduce the risk of declining the environmental quality of tidal swa,,!p area due to the agricultural activity, lhearea should be managed properly and Wisely especially when using agrochemicals such as fertilizers and pesticides. Inrelation to this, the use of biofertilizer such as Azotobacter spp, a nitrogen fIXing bacterium and IAA producer, might beimportant thingfor this area.The aims of this experiments was to study the ability of Azotobacter isolated from rice' rhizophere grown in tidalswamp area of South Kalimantan, in producing IAA to stimulate the growth of roots of rice cultivar I R-64. The parametersused to evaluate the effect of Azotobacter inoculation were the increase of the surface area of root, length of roots, totallength of roots, fresh, dry weight of rice IR-64 roots and the growth of root hairs.The results showed that Azotobacter produced less IAA in the media containing Urea (18.28-35.54 ppm IAA) comparedto Azotobacter grown in media without Urea (33.89 - 42.01 ppm IAA). Azotobacter T.M. UNST.3 produced the highest IAA(42.01 ppm), therefore they were able to increase the surface of roots, increase the length and weight of roots of rice cultivarIR-64 compared to other Azotobacter strains. In media containing Urea, Azotobacter RG 3.62 produced the least IAA (/8.29 ppm IAA) compared to other Azotobacter strains. However, this particular Azotobacter strain was able to increase the surface area of root, increased the number of root hairs compared to other strains.